Temporal information gaps and market efficiency: A dynamic behavioral analysis - Björn-Christopher Witte (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2009)
This study seeks to explore, how market efficiency changes, if ordinary traders receive fundamental news more or less often. We show that longer temporal information gaps lead to fewer but larger shocks and a reduction of the average noise level on the dynamics. The consequences of these effects for market efficiency are ambiguous. Longer temporal information gaps can deteriorate or improve market efficiency. The concrete result depends on the stability of the market together with the interval in which the length of the gap is incremented.
Keywords: G12; G14; 330; Temporal information gaps; market efficiency; disclosure policy; agent-based financial market models; technical and fundamental analysis; Effizienzmarktthese; Anlageverhalten; Asymmetrische Information; Auskunftspflicht; Wertpapieranalyse; Agent-based Model; Theorie